2018
DOI: 10.1038/s41598-018-20889-x
|View full text |Cite
|
Sign up to set email alerts
|

Updating the genomic taxonomy and epidemiology of Campylobacter hyointestinalis

Abstract: Campylobacter hyointestinalis is a member of an emerging group of zoonotic Campylobacter spp. that are increasingly identified in both gastric and non-gastric disease in humans. Here, we discovered C. hyointestinalis in three separate classes of New Zealand ruminant livestock; cattle, sheep and deer. To investigate the relevance of these findings we performed a systematic literature review on global C. hyointestinalis epidemiology and used comparative genomics to better understand and classify members of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 75 publications
4
24
0
Order By: Relevance
“…lawsonii could be reclassified as separate species within the genus Campylobacter. Indeed, a more recent study that performed whole-genome sequencing of 18 strains isolated from cattle, sheep, and deer from New Zealand confirmed the previously suggested genomewide plasticity of C. hyointestinalis (78). This work revealed high rates of gene gain/loss across C. hyointestinalis lineages, probably accounting for the effects of horizontal gene transfer.…”
Section: Campylobacter Hyointestinalissupporting
confidence: 71%
See 1 more Smart Citation
“…lawsonii could be reclassified as separate species within the genus Campylobacter. Indeed, a more recent study that performed whole-genome sequencing of 18 strains isolated from cattle, sheep, and deer from New Zealand confirmed the previously suggested genomewide plasticity of C. hyointestinalis (78). This work revealed high rates of gene gain/loss across C. hyointestinalis lineages, probably accounting for the effects of horizontal gene transfer.…”
Section: Campylobacter Hyointestinalissupporting
confidence: 71%
“…Together, the observed genomic variability of C. hyointestinalis may indicate a great potential to adapt to different ecological niches, underpinning its capacity to colonize a great variety of mammal species both as a commensal and as a disease-causing agent (78). Further comparisons between commensal and disease-associated strains may provide new insight into the genetic mechanisms underlying C. hyointestinalis pathogenicity.…”
Section: Campylobacter Hyointestinalismentioning
confidence: 99%
“…However, infection of children with non-thermophilic Campylobacter spp. (e.g., Campylobacter hyointestinalis, Campylobacter fetus, Campylobacter showae, and Campylobacter concisus) is largely underestimated due to unsuitable culturing methods and their public health risks specifically in EED pathogenesis is not known (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first comparative analysis of multiple C. hyointestinalis strains at whole-genome resolution confirmed the previously observed highly diverse nature of this bacterial species. This study revealed a great level of plasticity between C. hyointestinalis genomes, with high incidence of recombination and accessory gene gain/loss as the main factors contributing to the observed diversity within this species 16 . However, this study was mainly performed using C. hyointestinalis subsp.…”
Section: Discussionmentioning
confidence: 82%